Real Time and Recall Measures of Mobile Phone Use: Some Methodological Concerns and Empirical Applications - Cohen, Akiba A. and Lemish, Dafna (New Media & Society, 2003)
This article discusses the development, reliability, and validity of real-time measures of mobile phone use by means of Interactive Voice Response (IVR) technology, in comparison with traditional questionnaire-generated recall measures. The sample consisted of 211 Israeli adult mobile phone subscribers subdivided by gender and by the amount of airtime that they normally use. The measurements were applied to three questions to which the participants responded via IVR following their incoming and outgoing mobile phone calls during a five-day period: the identity of the person with whom they spoke; their location during the call; and the urgency of the call. These data were compared with recall measures obtained earlier from questionnaires. The article discusses the merits of the IVR real-time data versus those obtained from traditional recall questions asking for past or habitual behaviors.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNDYxNDQ0ODAzMDA1MDAyMDAy